Clinical performance of ASAS Health Index in patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis: real-world evidence from Multicenter Nationwide Registry - YAĞCI, İLKER; DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2020)
The Assessment of SpondyloArthritis international Society Health Index (ASAS HI) is used as a new instrument in measuring the function, disability and health of patients with spondyloarthritis (SpA). However, the real-world evidence of ASAS HI is very limited. In the present study, our objective is to evaluate the psychometric properties and performance of ASAS HI in the real-world setting as well as comparing ASAS HI with the current instruments to assess the construct validity and determine the cut-off points in patients with both ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA). A total of 991 patients with axSpA who fulfilled either the ASAS classification criteria for axial SpA (axSpA) or the Modified New York Criteria (mNY) for AS were recruited from the Biologic and targeted Synthetic antirheumatic drugs Registry (BioStaR) SpA. The construct validity of ASAS HI against the Bath Ankylosing Spondylitis Disease Activities Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score-C-Reactive Protein (ASDAS-CRP) the Bath Ankylosing Spondylitis Functional index (BASFI) was performed. Using the receiver operating characteristic (ROC) curves analysis, the cut-off points were calculated. Of all the recruited patients, 851 (85.9%) were AS and 140 (14.1%) were nr-axSpA. The difference in the mean ASAS HI scores of the patients with AS and the ones with nr-axSpA were not statistically significant (6.12 +/- 4.29 and 6.42 +/- 4.86, respectively). The mean ASAS HI score was significantly higher in females and small city residents. The ASAS HI had a strong construct validity against ASDAS-CRP, BASDAI and BASFI. A cut-off point of <= 4 was determined to discriminate good and moderate, as well as >= 12 to discriminate moderate and poor health status. In conclusion, ASAS HI is a reliable instrument to evaluate health and functioning for both patients with AS and nr-axSpA in clinical practice.
Keywords: Health Status Index; Ankylosing spondylitis; Health-related quality of life; Functional performance; QUALITY-OF-LIFE; CLASSIFICATION CRITERIA